2018
DOI: 10.3390/ma11071145
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Different Thickness Structure Combinations of Hot Mix Asphalt and Cement Emulsified Asphalt Mixtures

Abstract: Cement emulsified asphalt mixture (CEAM) is widely used in asphalt pavement for its environmental virtues. However, a CEAM layer can influence fatigue performance of asphalt pavement because of higher air voids of CEAM in contrast to hot mix asphalt (HMA). Therefore, it is common to use HMA and CEAM structure combinations for improving the fatigue performance. In this work, three different thickness structure combinations of HMA (AC-10) and CEAM (AC-16) were designed, in which HMA and CEAM were used as top lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In addition, the profile of the fatigue property with the pavement depths are consistent with the chemical, stiffness, and relaxation results. The differences in the fatigue properties with pavement depth may indicate the position where the fatigue damage occurs and the direction of the fatigue crack propagation (51,52).…”
Section: Change In the Rheological Properties Of Bitumenmentioning
confidence: 99%
“…In addition, the profile of the fatigue property with the pavement depths are consistent with the chemical, stiffness, and relaxation results. The differences in the fatigue properties with pavement depth may indicate the position where the fatigue damage occurs and the direction of the fatigue crack propagation (51,52).…”
Section: Change In the Rheological Properties Of Bitumenmentioning
confidence: 99%
“…This function maps the range of each input layer node (-∞, +∞) to that of each hidden layer node (-1, +1). As a differentiable function, it is suitable for training the samples at the node [13]. The output layer uses the linear transfer function purelin to excite and transfer the m input vectors, yielding a prediction matrix.…”
Section: Network Structurementioning
confidence: 99%
“…They discovered that when the tack coat material's stiffness grew, so did the asphalt pavements' fatigue life [7]. More recently, Wang et al (2018) [8] studied how varying tack coat thicknesses and materials affected the fatigue performance of asphalt pavements using FEM. Wang et al found that the fatigue life of asphalt pavements increased with increasing tack coat thickness and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al found that the fatigue life of asphalt pavements increased with increasing tack coat thickness and stiffness. They also discovered that the kind of tack coat material had a big impact on fatigue performance [8]. Braunfelds et al (2021) [9] conducted an experimental study on the use of fiber Bragg grating (FBG) optical temperature and strain sensors to monitor asphalt concrete layers under the load of a moving wheel for road structural health monitoring (SHM).…”
Section: Introductionmentioning
confidence: 99%